2014
DOI: 10.1186/1472-6920-14-96
|View full text |Cite
|
Sign up to set email alerts
|

Show what you know and deal with stress yourself: a qualitative interview study of medical interns’ perceptions of stress and gender

Abstract: BackgroundMedical students report high stress levels and in particular, the clinical phase is a demanding one. The field of medicine is still described as having a patriarchal culture which favors aspects like a physicians’ perceived certainty and rationalism. Also, the Effort-Recovery Model explains stress as coming from a discrepancy between job demands, job control, and perceived work potential. Gendered differences in stress are reported, but not much is known about medical interns’ perceptions of how gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 69 publications
3
38
0
Order By: Relevance
“…The findings of the present study are consistent with those of many other authors who report high levels of stress among medical students at the beginning of the program (Eva et al, 2015;Tavolacci et al, 2013;Verdonk, Rantzsch, de Vries, & Houkes, 2014). The stress questionnaire applied herein found a predominance of students in the resistance phase at both universities, a phase which is characterized as the extension of the alert phase.…”
Section: Discussionsupporting
confidence: 82%
“…The findings of the present study are consistent with those of many other authors who report high levels of stress among medical students at the beginning of the program (Eva et al, 2015;Tavolacci et al, 2013;Verdonk, Rantzsch, de Vries, & Houkes, 2014). The stress questionnaire applied herein found a predominance of students in the resistance phase at both universities, a phase which is characterized as the extension of the alert phase.…”
Section: Discussionsupporting
confidence: 82%
“…Gender differences have been evaluated across medical students to explore how they experience and cope with distress as well as what they think about the role of gender in distress 2 , 11 - 20 . According to literature reviews, 3 , 4 female medical students reported higher levels of depression, anxiety, and stress than their male peers 12 - 16 .…”
Section: Introductionmentioning
confidence: 99%
“…This is because differences in distress scores across gender groups must represent true differences in the construct of interest and not reflect the measurement bias. In previous studies, a variety of instruments have been used to assess depression, anxiety, and stress between male and female university students 4 , 10 - 14 , 19 , 20 , 23 - 25 . One of the most widely accepted instruments for assessing the severity of distress in clinical and non-clinical samples is Depression Anxiety Stress Scale-21 (DASS-21) 26 - 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Rather, like Whitehead and Goldie, we support curricula that facilitate students' ability to employ an appropriate competency at the most In this regard, the Practicum marks a transition in students' professional identify formation that is made obvious by a departure from didactic medical traineeship-centered on teaching technical competencies and professionalism-to experiential learning with real patients-often involving shadowing and observing practicing clinicians and other care providers. The literature suggests this transition from pre-clinical studentship to apprenticeship can be most disruptive to the status quo of medical traineeship characteristic of the first two years 25,26 . Indeed, apprehensions about inaugural encounters with patients and anxieties about meeting professional standards during clerkship were frequently discussed among our students.…”
Section: Doctor Who?mentioning
confidence: 99%
“…Patient exposure in various rotations can also highlight the reality that medicine-and by default physicians themselves-cannot save or cure patients in all cases 25 . Furthermore, some students may be less motivated to learn about administrative or extraprofessional aspects of care, for example, that do not involve direct interactions with patients 26,27 . The Practicum also aimed to imbue some of this learning as a result.…”
Section: Doctor Who?mentioning
confidence: 99%